PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN MASYARAKAT DI KUA KECAMATAN RUNGKUT KOTA SURABAYA - Anggraini, Lingga Heri (Universitas 17 Agustus 1945 Surabaya, 2017)
The influence the quality of service to the community satisfaction in KUA sub-district Rungkut, Surabaya City. Office of Religious Affairs (KUA), is an official state institution assigned to carry out some duties of the Indonesian religious ministry office in districts and cities for Islamic religious affairs within the district area. KUA facilities should ideally be of a reasonable quality in accordance with the duties and functions of KUA. It is very influential on KUA services to the community so that the visible satisfaction for the community at large. This study aims to determine and analyze the effect of service quality on community satisfaction in KUA Rungkut Subdistrict, Surabaya City. KUA facilities should ideally be of a reasonable quality in accordance with the duties and functions of KUA. It is very influential on KUA services to the community at large. This study aims to determine and analyze the effect of service quality on community satisfaction in KUA subdistrict Rungkut Surabaya City. Research method using questionnaire. Analysis techniques using interval analysis and correlation test. There are 100 respondens studied in this study by answering questions based in questionnaires given to assess public opinion about KUA services and their effect on community satisfaction. Independent variable is service quality and dependent variable is community satisfaction. The research result based on quantitative data processing through interval analysis and correlation test, the result of interval analysis shows the satisfaction of the community regarding the quality of service in KUA subdistrict Rungkut Surabaya good and satisfactory. The correlation test result of 0,868 and 0,932 indicates that the correlation of KUA service quality relationship and community satisfaction is very strong. This shows that the KUA subdistrict office members always try to provide the best service, systematic and professional for the community and try to give satisfaction to the community.Â Keywords: Service Quality, Communty Satisfaction, Office of Religious Affairs (KUA) Subdistrict Rungkut